Development of germplasm cryopreservation techniques for honey bee conservation - Pereira, Catarina Margarida Videira Dias (2020)
Cryopreservation is a recent tools that has enormous potential in all aspects of human life. With this tool, the limitations for preserving genetic material become almost impossible to grasp. With this dissertation there in an attempt to understand better how this new technology works and how to put it to good use in practical manners regarding honey bee conservation. This dissertation has two parts, the theoretical part and the practical part. The practical part was only possible to do in Länderinstitut für Bienenkunde, Berlin. When it comes to results found in this dissertation, data suggests that there is a better time for the collection of semen samples that obtain better results when put through cryopreservation protocols. We can also affirm that there is a possibility of sending semen samples by mail. The last conclusion regarding sperm analyses is that, there is no relationship between inbreeding factors and semen quality. Regarding the RNA experiments, even though they present to be a solid foundation for later experiments, by their preliminary nature, there is no definitive conclusion to be taken from them.